The Leadership Network in Public Service Assurance at Kedawung Community Health Center, Sragen Regency - Karno; Kartono, Rinikso (Journal of Local Government Issues, 2023)
The leadership is an important and needed factor in health services, therefore, the purpose of this study is to analyze the influence of leadership in health services at the Kedawung Community Health Center (Puskemas) on public service assurance for the community. Methods used quantitative research approaches and data were collected using questionnaires, observations, and literature studies. Data analysis was used SEM (Structural Equation Modeling) with a study population of 857 people, so that the research sample was 273 respondents. To strengthen the research used triangulation approach. The results showed that leadership has a significant influence on health services categorized as significant and positive with a pathway value of 0.59 greater than 0.5 and a t_value value of 4.49 greater than 1.96. The leadership has a dominant influence in health services at the Kedawung Puskemas is a relationship-oriented leadership dimension including indicators of patient protection, patient/patient family guidance, cooperation in serving patients, and increasing satisfaction of health service recipients. The existence of leadership has a significant effect on health services at the Kedawung Puskemas showing the importance of relationship-oriented leadership in achieving satisfactory health service performance for the community